1999
DOI: 10.1051/agro:19990104
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationships between species of the genus Prosopis revealed by the use of molecular markers

Abstract: of the relationships between species of the genus Prosopis revealed by the use of molecular markers. Agronomie, EDP Sciences, 1999, 19 (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…In the group average cluster analysis in this study, P. pallida and the hybrid formed a cluster with a similarity index of 0.582. In the group average dendogram, P. chilensis forms a cluster with P. alba and their clustering agrees with the result obtained by Ramirez et al (1999).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the group average cluster analysis in this study, P. pallida and the hybrid formed a cluster with a similarity index of 0.582. In the group average dendogram, P. chilensis forms a cluster with P. alba and their clustering agrees with the result obtained by Ramirez et al (1999).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, three RAPD primers A08, R18 and S07 yielded markers which were present in all the species belonging to Algarobia but absent in P. tamarugo belonging to section Strombocarpa. Ramirez et al (1999) described a similar identifiable marker using the primer S07. The group average clustering method separated P. tamarugo from the rest of the Prosopis species studied.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships observed among species in isoenzymatic (Saidman and Vilardi, 1993;Bessega et al, 2000a,b) and molecular (Ramírez et al, 1999;Saidman et al, 1998a,b;Saidman et al, 2000) analyses are not consistent with the series.…”
Section: Introductionmentioning
confidence: 96%
“…All of the species have 2«=28 except for some P. juliflora which are An [70]. Ramirez et al [139] examined RAPD profiles of species native to all four continents and were able to distinguish the species native to the individual continents. Analyses of nuclear ribosomal internal transcribed spacers among various series of Prosopis suggested that some species were monophyletic as a result of independent speciation that widely occurred in the New World [12].…”
Section: Prosopis and Mimosoid Tree Legumes With Heat And Salt Tolerancementioning
confidence: 99%